INDIGENOUS COMMUNITY, CUSTOMARY LAW AND MULTICULTURALISME IN INDONESIA - Zaenuddin Hudi Prasojo (Graduate Program of Pontianak Institute of Islamic Studies, 2013)
The awareness of awakening and efforts in reviving the customary law of indigenous communities in Indonesia has been going on for a long time, at least since the end of the reign of the New Order Regime. Customary law as one of the authentic capital of indigenous communities is a reflection of the existence of multicultural principles that have actually existed and been part of the Indonesian society. This work explores the case of cutomary law in West Kalimantan on Katab Kebahan’s practices in Melawi which is potential to be included to the National law. The role of customary law in the life of the multicultural society, like West Kalimantan society, in the modern era should be aligned with the history of the Unitary State of the Republic of Indonesia which was founded by the best children of the nations that agreed to establish a state based on the supremacy of law. Customary law is part of the state law. Therefore, there is s need to think of a proper format for the position and the role of customary law in the Indonesian legal system for the prosperity of society based on equality before the law and justice in accordance with the ideals of the nation. This paper suggests that, as an alternative as to where we might put the position of customary law in a multicultural nation today, we can take the example from patterns made by several countries that have adopted Restorative Justice systems with the main principles that the law is a device to resolve the problems in a just and fair way and with the awareness to return all the problems to the perspective of the law for the common good. Key words: cutomary law, mulitcultural society, restorative, justice